Biomarkers for Dementia, Fatigue, and Depression in Parkinson's Disease - Prell, Tino; Witte, Otto W.; Grosskreutz, Julian (Frontiers in Neurology, 2019)
Parkinson´s disease is a common multisystem neurodegenerative disorder characterized by typical motor and non-motor symptoms. There is an urgent need for biomarkers for assessment of disease severity, complications and prognosis. In addition, biomarkers reporting the underlying pathophysiology assist in understanding the disease and developing neuroprotective therapies. Ultimately, biomarkers could be used to develop a more efficient personalized approach for clinical trials and treatment strategies. With the goal to improve quality of life in Parkinson´s disease it is essential to understand and objectively monitor non-motor symptoms. This narrative review provides an overview of recent developments of biomarkers (biofluid samples and imaging) for three common neuropsychological syndromes in Parkinson´s disease: dementia, fatigue and depression.